Social sector development and inclusive growth in India - Chadda, Ishu (Diverse perspectives on creating a fairer society, 2023)
Many of India's most disadvantaged citizens face severe social and economic challenges. Social Sector Development and Inclusive Growth in India poses the essential question of whether growth strategies based on the human development approach, that is, social sector development, render growth inclusive. This comprehensive study considers all components of the social sector in aggregate and also covers both the financial and physical aspects to answer this question. Author Ishu Chadda examines the various World Bank reports and scholarly literature on this subject to quantify inclusiveness in India. Her research further highlights the major dimensions of inclusive development like poverty alleviation, employment generation, and access to equal participation. Chadda's research has been conducted to scrutinize the long-run and short-run association between the social sector and inclusive growth in India using the Autoregressive-Distributed Lag (ARDL) approach. Further, she looks at the relationship between social sector development and inclusive growth in India at a macro-level. Inclusive and sustainable economic growth is essential for a fair society and is thus a key component of the United Nations Sustainable Development Goals. This timely study will provide vital information to academic researchers and postgraduate students within as well as outside of the Indian context. Policy makers and practitioners of development studies, sociology and developmental economics will benefit from the key insights provided.